Choreographies - Pedro Ignacio Alonso; Hugo Palmarola (Diseña, 2018)
Choreographies is a work composed of two simultaneously running video loops, presented at the 4th Triennial of Architecture in Lisbon (2016). These videos show mostly children animation films from the US and the Soviet Union, in which steel beams and concrete panels are featured in the context of high-rise building construction. On many occasions, the role of the beams and panels was to provide continuity to the choreographies and to keep the characters from falling, configuring not only physical infrastructure roads, but also reliable conceptual paths that reflect an unflinching faith on American and Soviet supporting ideologies.